2017
DOI: 10.2131/jts.42.509
|View full text |Cite
|
Sign up to set email alerts
|

Mercury and selenium levels, and their molar ratios in several species of commercial shrimp in Japan regarding the health risk of methylmercury exposure

Abstract: The Japanese shrimp industry depends on importing shrimp from other countries. However, little information is available on mercury speciation and selenium (Se) concentrations in commercial shrimp available in Japan. The present study determined the concentrations of total mercury (T-Hg), methylmercury (MeHg), and Se in the muscles (wet weight) of imported and domestic commercial shrimp from Kumamoto and Kagoshima prefectures to obtain information for assessing the risk of MeHg exposure. The median concentratio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 17 publications
1
5
0
Order By: Relevance
“…Similarly, Hg concentrations in sardines were lower than the Hg levels in canned sardines (117 ng/g, 141 ng/g, and 143 ng/g) reported by Boadi et al (2011). The current study found that the percentage of MeHg in T-Hg in canned fish samples ranged from 90.4% to 100%, which was consistent with levels found in fish, squid and shrimp in previous studies (Bloom, 1992;Yoshimoto et al, 2016;Hoang et al, 2017).…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Similarly, Hg concentrations in sardines were lower than the Hg levels in canned sardines (117 ng/g, 141 ng/g, and 143 ng/g) reported by Boadi et al (2011). The current study found that the percentage of MeHg in T-Hg in canned fish samples ranged from 90.4% to 100%, which was consistent with levels found in fish, squid and shrimp in previous studies (Bloom, 1992;Yoshimoto et al, 2016;Hoang et al, 2017).…”
Section: Discussionsupporting
confidence: 88%
“…Recently, we reported that T-Hg, MeHg and Se concentrations in commercial shrimp in Japan, which included Vietnamese black tiger shrimp, were lower than the Japanese regulated level (Notice Kannyu No.99, 1973) of 300 ng/g for MeHg in fish (Hoang et al, 2017). Moreover, the average Se/Hg molar ratios in the muscle of commercial shrimp were comparatively high (in the range of 16-106).…”
Section: Discussionmentioning
confidence: 85%
“…T‐Hg concentrations in blood and sciatic nerve were measured with a direct thermal decomposition Hg analyzer (SP‐3D and MA‐3000; Nippon Instruments, Tokyo, Japan) as previously described (Yamamoto et al, ; Yamamoto et al, ). T‐Hg and MeHg contents in brain tissue were measured using a protocol we developed previously (Hoang, Do, et al, ; Hoang, Sakamoto, & Yamamoto, ; Miyamoto, Kuwana, Ando, Yamamoto, & Nakano, ; Yoshimoto et al, ). The samples were solubilized with 0.1% Cys solution (1 mL) and 5 m NaOH (1 mL), then incubated at 80°C for 1 hour with vortexing every 10 minutes.…”
Section: Methodsmentioning
confidence: 99%
“…The mobility, toxicity, and bioavailability of trace elements depend strongly on their particular existing forms in a given system. For example, organic mercury, especially MeHg, is more toxic to marine animals than inorganic mercury due to its facilitated penetration of biological membranes, its high stability, and biomagnification capacity (Hoang, Sakamoto, & Yamamoto, ). One of the toxic aspects of mercury is attributed to the very strong affinity between Hg 2+ or MeHg + and Se 2− .…”
Section: Introductionmentioning
confidence: 99%
“…Based on this affinity, the toxic mechanisms of mercury are strongly related to the concentration of selenium in ecosystems and organisms. It could have an increasing potential for the toxic effects when the molar mercury concentration exceeds that of selenium, that is, Se:Hg < 1 (Hoang et al., ; Mulder et al., ). Therefore, the existing forms and proportions along with the mutual bioaccumulation of selenium and mercury in organisms and the environment have attracted extensive attention of researchers.…”
Section: Introductionmentioning
confidence: 99%